THE TEACHING OF SPEAKING AT “MR PEPSI ENGLISH COURSE” IN KAMPUNG INGGRIS PARE KEDIRI - Ahmad Latif Mahruf (Graduate Program, University of Islam Malang, 2019)
AbstractTeaching speaking as a foreign language is a complicated activity. Teachers perform some efforts to achieve oral competence in English. The teachers should prepare a good lesson plan, appropriate teaching strategies, and speaking assessment. A lesson plan is considered a crucial part of teaching speaking because it contains the objectives of the course, teaching and learning activities, and the assessment to check students’ understanding of the lesson. This research is conducted to describe the process of teaching speaking activity in informal English institution. This study was intended to answer the research problems: What is the planning to teach speaking skill, What is the teaching strategy to teach speaking skill, and What is the assessment to assess speaking skill. Therefore, this study had some objectives to investigate the planning, teaching strategies, and assessment activity in teaching speaking. The research was conducted using qualitative design which focuses on a case study. The research site was at Mr. Pepsi English course kampung inggris Pare Kediri due to some special treatment given by the teacher in teaching speaking. The researcher selected this course since the course program focus on speaking skill. A qualified teacher who has been teaching within three years and teach the impromptu program at the course was required as the research subject. To collect the data, the researcher conducted observation, interview, and documentation. The findings revealed that the teacher planned the teaching activities by designing a lesson plan as guidance in the class. The strategies used by the teacher to teach speaking are an oral presentation, discussion, dialogue, and reading aloud. In addition, an assessment for speaking skill was interview practice. Some suggestions addressed to English teacher, government, and future research on the basis of the result. EFL teaching practitioners should improve the ability to design a lesson plan and selecting strategies for teaching speaking. Assessment activity should be related to the objectives of the course. Also, the government should provide training and workshop to enhance the quality of the EFL teacher. For the next researcher, conducting a study in the same research design is suggested by using different skills and set of place.Key Words: speaking comprehension, teaching speaking, English course